Os sentidos do trabalho: a experiência de trabalhadoras de facções de costura da indústria de confecções no Ceará - Matos, Juliane Oliveira (2008)
According to the necessities of flexibilization in production, enterprises have been minimizing his board of effective workers and outsourced part of the productive process. In case of the textile industry, the factories subcontract small productive unities, called sewing factions. With that, they resist better to the market sazonality and get rid of labor taxes and responsibilities. Meantime, the costs of this process falls back on the dressmakers who works in the sewing factions, since they work generally in informality, without labor secured benefits, having to deal with the instability of the market. In this perspective, the present work looked to know, through the experience of the dressmakers, which sense they attribute to his work due to the conditions found in the sewing factions and how they drive themselves in front of labor relations that they experiment. The informations were gathered by interviews, having these been subjected to an content analysis. It was possible to identify the construction of a perverse and deceitful logic, in which the labor rights are exchanged for the sensation of a free work, what in fact contributes to aggravate the feminine work segregation in activities more vulnerable of the labor market. The proliferation of sewing factions in the productive sector of the textile industry, especially in the Industrial District of Maracanaú - Ceará, confirms the global tendencies in transformation of work organization that brings the enlargement of precarious work, supported by the strategy of subemployment and the use of informal work.